A Comparison of STAD and Drill Strategy in Increasing Grade V Students’ Cognitive Achievement on Ratios - Dorothy Rimba; Dylmoon Hidayat (Universitas Pelita Harapan, 2016)
This research is aimed at determining whether grade V students’ cognitive achievement increase using STAD and drill strategy. This research is also aimed at comparing STAD and drill strategy in increasing the cognitive achievement of grade V students on the topic of ratios in mathematics. The design of this research is a pretest-posttest two-group design. The sampling is done randomly. Descriptive statistics and non-parametric statistics are used to analyze the data. Using SPSS, the results showed that the grade V students’ cognitive achievement on ratios increased after studying mathematics using STAD and drill strategy. However, there was no significant difference in results between STAD and drill strategy in increasing the student’s cognitive achievement. Therefore, the grade V students’ cognitive achievement in both classes increased at a similar level using STAD and drill strategy.BAHASA INDONESIA ABSTRAK: Penelitian ini bertujuan untuk mengetahui apakah pencapaian kognitif siswa kelas V dapat meningkat menggunakan STAD dan drill strategy. Penelitian ini juga bertujuan untuk membandingkan STAD dan drill strategy dalam meningkatkan pencapaian kognitif siswa kelas V pada topik perbandingan dalam pembelajaran matematika. Desain dari penelitian ini adalah pretest-posttest two group design. Pengambilan sample dilakukan secara random. Statistik deskriptif dan statistik non-parametrik adalah teknik yang digunakan untuk menganalisis data pada penelitian ini. Dengan menggunakan SPSS, penelitian ini menunjukkan bahwa pencapaian kognitif siswa kelas V pada topik perbandingan meningkat setelah pembelajaran matematika menggunakan STAD dan drill strategy. Namun, tidak ada perbedaan antara STAD dan drill strategy dalam meningkatkan pencapaian kognitif siswa kelas V pada topik perbandingan. Maka dari itu, pencapaian kognitif siswa kelas V pada kedua kelas meningkat pada tingkatan yang hampir setara dengan menggunakan STAD dan drill strategy.